2015
DOI: 10.1016/j.scr.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing reproductive toxicity of two environmental toxicants with a novel in vitro human spermatogenic model

Abstract: Environmental influences and insults by reproductive toxicant exposure can lead to impaired spermatogenesis or infertility. Understanding how toxicants disrupt spermatogenesis is critical for determining how environmental factors contribute to impaired fertility. While current animal models are available, understanding of the reproductive toxic effects on human fertility requires a more robust model system. We recently demonstrated that human pluripotent stem cells can differentiate into spermatogonial stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…We have demonstrated that bovine testicular iPSCs are useful for screening the toxicity of environmental disruptors, such as phthalate esters by examining their effects on the maintenance of stemness and pluripotency, and for identifying signaling pathways that might be affected by disruptors [ 36 , 37 ]. Modeling spermatogenesis in vitro has been employed to examine the effects of environmental toxicants on the differentiation process to spermatozoa [ 38 ]. This represents a unique platform for assessing the toxicity of various environmental disruptors on human reproductive functions in a rather straightforward manner.…”
Section: Male Germ Cell Generation In Vitromentioning
confidence: 99%
“…We have demonstrated that bovine testicular iPSCs are useful for screening the toxicity of environmental disruptors, such as phthalate esters by examining their effects on the maintenance of stemness and pluripotency, and for identifying signaling pathways that might be affected by disruptors [ 36 , 37 ]. Modeling spermatogenesis in vitro has been employed to examine the effects of environmental toxicants on the differentiation process to spermatozoa [ 38 ]. This represents a unique platform for assessing the toxicity of various environmental disruptors on human reproductive functions in a rather straightforward manner.…”
Section: Male Germ Cell Generation In Vitromentioning
confidence: 99%
“…Numerous environmental toxicants (e.g. cadmium, mercury, bisphenol A (BPA) and dioxin) have been reported to adversely affect spermatogenesis in rodents and humans, which can lead to low sperm count, abnormal sperm morphology and poor semen quality (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known to cause reproductive toxicity and developmental disorders in animals, causing oligospermia and testicular atrophy. Male workers exposed to DBCP during the chemical manufacturing process similarly showed testicular toxicity in proportion to the exposure dose [45,46]. Workers exposed to high doses of DBCP had damage to spermatogonia and irreversible azoospermia [47].…”
Section: Reproductive Toxic Agents In Malesmentioning
confidence: 99%